Psalms ; v. 2 an expositional commentary - Boice, James Montgomery, 1938-2000 (Grand Rapids, MI Baker, 1996)
Contents : v. 2 : Psalms 42-106 Includes bibliographical references and indexes.
Keywords: Bible. O.T. Psalms XLII-CVI -- commentaries